Seasonal food habits of livestock in south Turkana, Kenya - Coppock, D. Layne; Ellis, J.E.; Swift, D.M. (1987)
A study carried out to quantify the diet composition for Ngisonyoka livestock in Kenya throughout one annual cycle and to identify plant species of critical importance to this system.